A Simultaneous Equations Model for World Crude Oil and Natural Gas Markets - Krichene, Noureddine (IMF Working Papers; Working Paper, 2005)
A model for world crude oil and natural gas markets is estimated. It confirms low price and high income elasticities of demand for both crude oil and natural gas, which explains the market power of oil producers and price volatility following shocks. The paper establishes a relationship between oil prices, changes in the nominal effective exchange rate (NEER) of the U.S. dollar, and the U.S. interest rates, thereby identifying demand shocks arising from monetary policy. Both interest rates and the NEER are shown to influence crude prices inversely. The results imply that crude oil prices should be included in the policy rule equation of an inflation targeting model.